Jardiner les décombres - Julie Scapino (Revue d'ethnoécologie)
In northern cities, urban agriculture is from now on at the heart of sustainable and resilient cities projects. This article proposes an ethnography of a vegetable appropriation led by a group of artists and “activists of vegetal” on the railway brownfield site of the Parisian petite ceinture. Inspired by the permacultural model, these urban gardeners play with a nourishing nature in a space antinomic with life, by orchestrating a return to nature on the ruins of our industrial and artificialised society.